Economic Viability Investigation of Mixed-Biomass Briquettes Made from Agricultural Residues for Household Cooking Use - Bill Vaneck Bot; Petros J. Axaopoulos; Evangelos I. Sakellariou; Olivier Thierry Sosso; Jean Gaston Tamba (Energies, 2023)
This paper presents a theoretical evaluation of the prices of mixed briquettes produced from coconut shells (CCS), banana peels (BNP), rattan waste (RWT), and sugarcane bagasse (SGC) and, on the other hand, an analysis of the economic viability of their use as a replacement for conventional household fuels (liquefied petroleum gas, fuelwood, and wood charcoal) in households in Cameroon. The investigation was carried out using the life cycle cost method on a typical household over a ten-year period with annual cooking energy requirements of 950 kWhth. The SGC–CCS and SGC–RWT mixed briquettes with ratios higher than 7.75% and 11.1%, respectively, have prices lower than EUR 0.063/kWhth. The Present Value of the Net Benefit is positive for the use of SGC–CCS and SGC–RWT mixed briquettes. The results show that by making the right mixes of residues, it is possible to obtain biomass briquettes that are less expensive than conventional fuels.